Analisis Strategi Pengembangan Sumber Daya Manusia di PT JVC Kenwood dalam Meningkatkan Produktivitas Karyawan - Cesa Putri Septiningtyas; Puji Isyanto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the human resource development (HRD) strategies implemented at PT JVC KENWOOD and their impact on employee productivity. The method used is descriptive qualitative, with data collected through interviews, observation, and document analysis. The research findings indicate that HR development strategies such as continuous training, coaching, and periodic performance evaluations have positively contributed to improving employees' skills and work efficiency. However, challenges remain in utilizing training technology and measuring program effectiveness. Therefore, continuous evaluation is needed to ensure that HR strategies are optimized in supporting the company's productivity.